Antiviral Activity of Propyl Gallate against Replication of Dengue Virus Serotype 2: In Vitro and In Silico Study - Soetedjo, Ariel Valentino; Desti, Hidayati; Dewi, Beti (Open Access Macedonian Journal of Medical Sciences, 2023)
Introduction: Dengue fever (DF) and dengue hemorrhagic fever (DHF) are infectious diseases caused by dengue virus (DENV) with high mortality rates. The mainstay of treatment for DENV infection is supportive, since there were no commercial specific antiviral drug for DENV. Propyl gallate has potential to be an antivirus for DENV. However, the mechanism is still unknown. This study aims to identify the activity of propyl gallate in DENV-2 replication in vitro and analyze the binding energy of propyl gallate towards NS3 and NS5 protein in silico. Methods: We used DENV serotype 2 New Guinea C and Vero cells for in vitro study. Focus and MTT assay was conducted to measure inhibition percentage and to measure viability percentage. Furthermore, in silico was conducted to identify the binding energy and inhibition constant of propyl gallate towards NS3 dan NS5 protein. Results: The percentage inhibition of pre and post infection was 4,34±7,53% and 30,7±4,88% with viability of 94,64±0,4% and 95,31±3,38%, respectively. The binding energy of propyl gallate with NS5, NS3 protease, and NS3 helicase were -3,49 kcal/mol, -2,47 kcal/mol, and -3,72 kcal/mol. Conclusion: Propyl gallate has high inhibition activity towards DENV-2 adhesion-replication in vitro with low binding energy to NS5 and NS3 in silico.